The Effect of Hypolipidemic Agents on Thyroid Autoimmunity in Women with Hashimoto’s Thyroiditis Treated with Levothyroxine and Selenomethionine - Krysiak, Robert; Szkróbka, Witold; Okopień, Bogusław (Experimental and Clinical Endocrinology & Diabetes, 2018)
Background Levothyroxine and selenomethionine were found to reduce thyroid antibody titers in patients with Hashimoto’s thyroiditis. The same effect was produced by intensive statin therapy. The aim of the present study was to assess whether hypolipidemic agents modulate the impact of thyroid hormone supplementation and selenomethionine on thyroid autoimmunity.Methods The study included 62 women with Hashimoto's thyroiditis treated for at least 6 months with levothyroxine and selenomethionine. On the basis of plasma lipids, women were divided into three groups: women with isolated hypercholesterolemia (group A; n=20), women with isolated hypertriglyceridemia (group B; n=17), and women with normal plasma lipids (group C; n=25). Group A were then treated with atorvastatin (20 mg daily), while group B received micronized fenofibrate (200 mg daily). Serum titers of thyroid peroxidase and thyroglobulin antibodies, as well as serum levels of thyrotropin, free thyroxine and free triiodothyronine were measured at the beginning of the study and 6 months later.Results Fenofibrate decreased triglycerides and increased HDL cholesterol, while simvastatin decreased total and LDL cholesterol. Fenofibrate reduced titers of thyroid peroxidase and, to a lesser extent, thyroglobulin antibodies. Atorvastatin tended to increase thyroid peroxidase antibodies. No changes in thyrotropin, free thyroxine and free triiodothyronine were observed in any treatment group. Fenofibrate-induced changes in thyroid antibody titers correlated with baseline antibody titers, as well as with treatment-induced changes in HDL cholesterol and insulin sensitivity.Conclusions The obtained results indicate that only fibrates may potentiate the effect of selenomethionine and levothyroxine on thyroid autoimmunity in women.
Keywords: fibrates; hypothalamic-pituitary-thyroid axis; levothyroxine; statins; thyroiditis